Takhrij and Syarah Hadith of Chemistry: Prohibition of blowing Food and Drinks - Amelia Putri Sugiso; Annisaa Siti Zuadah; Wahyudin Darmalaksana; Eko Prabowo Hadisantoso; R Yuli Ahmad Hambali (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about blowing hot food and drink in Islamic and scientific view. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this research are the dangers of blowing hot food and drinks according to a scientific perspective. The conclusion of this research is takhrij and syarah hadith regarding the prohibition of blowing hot food and drinks in the view of Islam and science.